2015
DOI: 10.1007/s00330-015-3834-9
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral perfusion in the predementia stages of Alzheimer’s disease

Abstract: ObjectivesTo investigate arterial spin-labelling (ASL) cerebral blood flow (CBF) changes in predementia stages of Alzheimer’s disease (AD).MethodsData were obtained from 177 patients with subjective complaints, mild cognitive impairment and AD from the Amsterdam Dementia Cohort. AD stages were based on diagnosis and cerebrospinal fluid biomarkers amyloid-β (Aβ) and total-tau (tau). General-linear-models were used to assess relationships between AD stages and total and regional CBF, correcting for age and sex.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
89
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 34 publications
(46 reference statements)
13
89
2
Order By: Relevance
“…In concordance with previous ASL studies [7][8][9][10][11]16], highest accuracies for SVM training were observed using AD-specific ROIs instead of whole-brain. For AD vs. SCD, the combined parietal lobe and hippocampus ROI yielded the highest accuracy.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In concordance with previous ASL studies [7][8][9][10][11]16], highest accuracies for SVM training were observed using AD-specific ROIs instead of whole-brain. For AD vs. SCD, the combined parietal lobe and hippocampus ROI yielded the highest accuracy.…”
Section: Discussionsupporting
confidence: 90%
“…Although the use of the parietal lobe is in line with previous ASL results [10,11], application of the occipital lobe is contradictive, as occipital hypo-perfusion has been observed in patients with MCI compared to controls, but not compared to patients with AD [11,13]. The fact that the majority of our AD sample consisted of early-onset AD patients, who present with a more pronounced overall and occipital hypo-perfusion and hypo-metabolism compared to late-onset AD patients [33,34], could explain this discrepancy.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations